(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
Solor as leading trades of sandalwood in Indonesia at past caused its territory to be the target of power by many parties like Majapahit, Ternate, Belanda and Portugis. Besides motivated to control Solor, they also expanded the influence in terms of politics, economics and even religion. So it is not surprising that the legacy traces were shown clearly by their influence on Solor society life. The results show that such influence ultimately leads to the emergence of a multicultural Solor society. The multiculturalism of Solor society reflected by various things such as ethnic, religious and linguistic diversity.